Regulation of a phenylalanine ammonia lyase ( BbPAL ) by calmodulin in response to environmental changes in the entomopathogenic fungus B eauveria bassiana - Jiyoung Kim; Hyesung Park; Jae‐Gu Han; Junsang Oh; Hyung‐Kyoon Choi; Seong Hwan Kim; Gi‐Ho Sung (Environmental Microbiology, 2015)
Summary Phenylalanine ammonia lyase ( PAL , E. C . 4.3.1.5) catalyses the deamination of L ‐phenylalanine to trans ‐cinnamic acid and ammonia, facilitating a critical step in the phenylpropanoid pathway that produces a variety of secondary metabolites. In this study, we isolated BbPAL gene in the entomopathogenic fungus B eauveria bassiana . According to multiple sequence alignment, homology modelling and in vitro PAL activity, we demonstrated that BbPAL acts as a typical PAL enzyme in B . bassiana . BbPAL interacted with calmodulin ( CaM ) in vitro and in vivo , indicating that BbPAL is a novel CaM ‐binding protein. The functional role of CaM in BbPAL action was to negatively regulate the BbPAL activity in B . bassiana . High‐performance liquid chromatography analysis revealed that L ‐phenylalanine was reduced and trans ‐cinnamic acid was increased in response to the CaM inhibitor W ‐7. Dark conditions suppressed BbPAL activity in B . bassiana , compared with light. In addition, heat and cold stresses inhibited BbPAL activity in B . bassiana . Interestingly, these negative effects of BbPAL activity by dark, heat and cold conditions were recovered by W ‐7 treatment, suggesting that the inhibitory mechanism is mediated through stimulation of CaM activity. Therefore, this work suggests that BbPAL plays a role in the phenylpropanoid pathway mediated by environmental stimuli via the CaM signalling pathway.